2016
DOI: 10.1200/jco.2016.66.9697
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Placebo-Controlled Phase III Study of Tasquinimod in Men With Metastatic Castration-Resistant Prostate Cancer

Abstract: Tasquinimod, a novel oral therapy targeting the tumor microenvironment, significantly improved progression-free survival (PFS) in a randomized, placebo-controlled phase II trial in men with metastatic castration-resistant prostate cancer (mCRPC). This phase III study was conducted to confirm the phase II results and to detect an overall survival (OS) benefit. Patients and MethodsMen with chemotherapy-naïve mCRPC and evidence of bone metastases were assigned (2:1) to receive tasquinimod once per day or placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 27 publications
1
54
0
Order By: Relevance
“…The clinical trial report of ribociclib, a drug for breast cancer, mentions in its discussion that “Most patients had an acceptable adverse-event profile.”1 A report of a trial of liposomal irinotecan in pancreatic cancer states in the concluding paragraph that it “has a manageable and mostly reversible safety profile.”2 And a trial of tasquinimod in patients with prostate cancer reports “the tolerability was good overall.”3…”
mentioning
confidence: 99%
“…The clinical trial report of ribociclib, a drug for breast cancer, mentions in its discussion that “Most patients had an acceptable adverse-event profile.”1 A report of a trial of liposomal irinotecan in pancreatic cancer states in the concluding paragraph that it “has a manageable and mostly reversible safety profile.”2 And a trial of tasquinimod in patients with prostate cancer reports “the tolerability was good overall.”3…”
mentioning
confidence: 99%
“…Tasquinimod is an investigational drug being evaluated in metastatic castration-resistant prostate cancer (mCRPC) and other solid tumor types. Unfortunately, tasquinimod failed to increase OS when given at 1 mg/day in a recent phase III trial of men with chemotherapy-naïve mCRPC, but did significantly improve radiographic PFS in this population [27]. It should be noted that this dose achieves a C max of ~0.5 μM, which is suboptimal based on an IC50 for this agent of ~0.5–1 μM [22].…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, placebo‐controlled phase 2 study of men with mCRPC, tasquinimod significantly improved PFS (7.6 months for tasquinimod and 3.3 months for placebo, P < 0.01) . However, an international, double‐blind, placebo‐controlled, phase 3 trial of chemotherapy‐naïve men with mCRPC showed no significant OS benefit (21.3 months for tasquinimod and 24 months for placebo, P = 0.25) . Despite these results, there remains interest in the use of tumor microenvironment disruptors in combination with other immunotherapies.…”
Section: Tumor Microenvironment Disruptorsmentioning
confidence: 99%